'Who are you today?' Problems of identity in psychiatry. (August 2020) - Foster, Charles
Abstract : Our attributes change. Sometimes they are changed so dramatically (for instance by organic brain disease, traumatic brain injury or psychiatric disease) that it is hard to see any significant continuity with the premorbid person. Sometimes this can have important ethical and legal consequences, but the problems are often ignored. This article highlights some of the difficulties.